Utilization pattern and survival outcomes of adjuvant therapies in high‐grade nonretroperitoneal abdominal soft tissue sarcoma: A population‐based study. Issue 1 (2nd May 2017) - Green, William Ross; Chokshi, Ravi; Jabbour, Salma K.; DeLaney, Thomas F.; Mahmoud, Omar
Abstract: Background: Nonretroperitoneal abdominal soft tissue sarcoma (NRA‐STS) is a rare disease with limited data supporting its management. Our study aimed to reveal the utilization patterns of adjuvant therapy and its potential survival benefits using the National Cancer Data Base. Materials: The analysis included patients with resected high‐grade NRA‐STS. Chi‐square analysis was used to evaluate distribution of patient and tumor‐related factors within treatment groups. The Kaplan–Meier and Cox proportional hazards model were utilized to evaluate overall survival according to treatment approach. Multivariate analysis was used to determine the impact of these factors on patients' outcome. Matched propensity score analysis was implemented to control for imbalance of confounding variables. Results: At median follow‐up of 49 months, 5‐year overall survival improved from 46% without adjuvant radiation therapy to 52% ( P = 0.009) with radiotherapy delivery with a 30% reduction in hazard of death (95% confidence interval = 0.58–0.84). On multivariate analysis, age <50, tumor <8 cm, negative margins and radiotherapy delivery were significant predictors of improved survival. Chemotherapy was not associated with significant survival improvement (Hazard Ratios [HR]: 0.89, P = 0.28). Conclusion: Adjuvant radiotherapy was associated with improved survival in high‐grade NRA‐STS. Chemotherapy was not associated with a survival improvement; however, further studies are needed to refine treatment strategies.